Historical Thinking Skills and Critical Thinking Skills - Nurjanah, Wulan (HISTORIKA, 2020)
AbstractHistorical thinking skills is very important for students because it can improve critical thinking skills for students. Critical thinking skills are the characteristics of global citizens, multicultural, and democratic societies that will equip students to be prepared and aware of future academic, civil and social challenges. Through the development of historical thinking skills in learning it is hoped that later students will have the skills to review their environment more critically and determine their own future and influence decisions relating to their destiny.